THE IMPACT OF JOB STRESS, JOB INSECURITY, AND WORK ENGAGEMENT ON JOB PERFORMANCE AMONG HOTEL INDUSTRY EMPLOYEES IN SIEM REAP, CAMBODIA, DURING THE COVID-19 PANDEMIC - Ol, Elite; Sattayawaksakul, Damrong (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2025)
Prior studies have explained how job stress, job insecurity, and work engagement influence job performance under normal conditions. However, there have been limited empirical studies during an unprecedented crisis. This study examined the impact of job stress, job insecurity, and work engagement on job performance during the COVID-19 pandemic among the hotel industry employees in Siem Reap, Cambodia. Data were collected from 212 respondents who were hotel industry employees in Siem Reap. The collected data were analyzed using descriptive statistics, Pearson’s correlation coefficient, simple regression, and multiple regression analysis. The results revealed that job stress and job insecurity had a statistically significant impact on job performance (Job stress: Beta = 0.179, p = 0.000; Job insecurity: Beta = 0.414, p = 0.000). In addition, job stress and job insecurity had a statistically significant impact on work engagement (Job stress: Beta = -0.157, p < .05; Job security: Beta = 0.830, p = 0.000). Finally, work engagement had a statistically significant impact on job performance (Beta = 0.502, p = 0.000). The results of this research can be used to help employers understand the factors that influence employees' job performance if similar events occur in the future. The study recommends several improvements for employees and employers in the hotel industry in Siem Reap. These include communication with each other, minimizing utilities and other expenses during a pandemic, controlling employees’ emotions when problems arise, and improving employees’ work performance rather than worrying about issues that may occur in the future.